A Prima Facie assessment of the prevalence of certain emotional biases in the investment decisions of South African students - Brandt, Richard (Department of Finance and Tax, 2017)
This study investigates the prevalence of emotional biases that influence South African students' decision-making in an investment context. This study advances the understanding of whether the future financial professionals of South Africa are susceptible to irrational decision-making due to the influence of emotional biases. A questionnaire-based survey was employed to test whether a sample of South African finance students exhibit emotional biases that influence their investment decision-making. The questionnaire posited investment scenarios to which the students would answer intuitively based on the information that was provided to them. This study asked the students to respond using their "gut-feel" to test whether emotional biases were inherent in their decision-making process. It was found that the respondents were influenced by market trends, otherwise known as the representative bias, making them more susceptible to notice patterns in truly random sequences of data, or making them think that future patterns will resemble previous patterns. 85% of respondents did not show a tendency to anchor to a particular reference point. However, the data showed that 15% of the respondents did not give an answer when asked to answer intuitively, while 100% of the students gave a response when a reference point was introduced. Just over half of respondents exhibited traits of overconfidence, and, consistent with historical research, males exhibited greater overconfidence than females. However, male and female responses showed mixed results in respect of loss aversion scenarios. Furthermore, the analysis revealed that 58% of respondents were partial to choosing options that were framed positively. Finally, there was no significant evidence that respondents were influenced by the herding bias or the illusion of control bias. In summary, this study found at least prima facie evidence of some emotional biases that influence investment decision-making. This conclusion demonstrates a viable basis for future research on the role of emotion (and, pertinently, emotional intelligence) in investment decision-making.